Analisis Pengaruh Dimensi Work-Life Balance Terhadap Intensi Turnover Karyawan pada Generasi Milenial (Y) - Boy Andika Sinaga; Rikardo E Parapat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research was to find and analyze the influencing factors of turnover in milenial’s generation employees (Y) using work-life balance aspect. This research was carried out quantitatively, using the survey methode with data analysis techniques using multiple linear regression methods. Quaestionnaire as a data collection instrument and distributed online via google form used 109 respondents. The dimensions of measuring the work-life balance aspect are work interference with personal life, work enhancement of personal life, personal life interference with work, personal life enhancement of work, and satisfaction balance. This research results obtained are the work interference with personal life which has significant effect on millennial employee turnover. While the others four dimensions are also quite influential on turnover. For decreasing turnover, companies need to create support policies to create work-life balance by implementing such as flexible working hours and being committed to balancing work and personal lives of employees.